METALLIC BIOMATERIALS: STAINLESS STEEL, TITANIUM AND ITS ALLOYS, AND COBALT-BASED ALLOYS - Tobisawa, Rodrigo Yugi Ikuta; Lourenço, Rayana Fernanda Ribeiro; Silva, Gilbert; Fernandes, Gerson Avelino (Seven Editora, 2025)
Metallic biomaterials have extensive uses and applications in medicine, primarily in bone replacements and repairs, metal plates for fractures, and dental implants, as well as tissue replacement. The use of metals in biomaterials provides greater corrosion resistance, mechanical strength, and biocompatibility. The main metallic biomaterials are stainless steel, cobalt-based alloys, and titanium and its alloys. The objective of this work was to study the properties that allow these metals to be used in biomedicine, where the performance of each metallic biomaterial was assessed, as well as their properties. The importance of different metallic alloys and their properties was also highlighted. DOI: https://doi.org/10.56238/sevened2025.029-092